Different intensities of aerobic training for patients with type 2 diabetes mellitus and knee osteoarthritis: a randomized controlled trial - Su, Chi; Huang, Lihua; Tu, Shaochen; Lu, Shengdi (Frontiers in Endocrinology, 2024)
Objective The purpose of this study was to compare different intensity of aerobic exercise for patients with KOA and T2DM in terms of glycemic control, pain relief, and functional outcomes. Methods A prospective, randomized, open-label, parallel, multi-center clinical trial conducted at two hospitals in Shanghai and Sichuan that included 228 patients type 2 diabetes mellitus (T2DM) and knee osteoarthritis (KOA). Enrollment occurred between January 2021 and February 2023, and follow-up was completed September 2023. Participants were randomized to threshold training/high-intensive stationary cycling training (n=76), intensive endurance/moderate-intensive stationary cycling training (n=77) and regular rehabilitation programs (n=75). Primary outcomes at the 6-month follow-up were level of HbA1c, key secondary outcomes included Knee Injury and Osteoarthritis Outcome Score (KOOS) knee pain and function. Results Among 228 patients, 212 (93%) completed the trial. Mean adjusted (sex, baseline BMI, baseline outcome measures) HbA1c level at 6-month follow-up decreased significantly in high-intensive training group than other groups (High-intensity group vs control group, difference 0.51%, 95% CI, 0.05% to 1.15%). Mean KOOS subscales of pain and quality of life were statistically significantly different between control group and moderate-intensity group or high-intensity group, but no statistically difference were noted between different intensity of aerobic exercise. Patient in all groups achieved a greater reduction in BMI but no significant differences were observed between groups as well. Conclusion Among patients with KOA and T2DM, high-intensity stationary cycling has significantly capability of glycemic control than moderate-intensity and regular rehabilitation program. But high-intensity stationary cycling has no superior effect on pain relief and functional improvement for KOA when compared to moderate-intensity and regular rehabilitation program.